Incidental Findings on CT Scans in the Emergency Department - Ryan J. Thompson; Susan M. Wojcik; William D. Grant; Paul Y. Ko (Emergency Medicine International)
Objectives. Incidental findings on computed tomography (CT) scans are common. We sought to examine rates of findings and disclosure among discharged patients who received a CT scan in the ED. Methods. Retrospective chart review (Aug-Oct 2009) of 600 patients age 18 and older discharged home from an urban Level 1 trauma center. CT reports were used to identify incidental findings and discharge paperwork was used to determine whether the patient was informed of these findings. Results. There were 682 CT scans among 600 patients: 199 Abdomen & Pelvis, 405 Head, and 78 Thorax. A total of 348 incidental findings were documented in 228/682 (33.4%) of the scans, of which 34 (9.8%) were reported to patients in discharge paperwork. Patients with 1 incidental finding were less likely to receive disclosure than patients with 2 or more (𝑃=.010). Patients age <60 were less likely to have incidental findings (𝑃<.001). There was no significant disclosure or incidental finding difference by gender. Conclusions. While previous research suggests that CT incidental findings are often benign, reporting to patients is recommended but this is rarely happening.